Medial Patellofemoral Ligament Reconstruction: A Comprehensive Review - Kyung, Hee-Soo (Knee Surg Relat Res, 2015)
It has been suggested that in the majority of patellar dislocation cases, the medial patellofemoral ligament (MPFL) is disrupted with a high recurrence rate especially in female patients. Although MPFL tear is not the primary cause of instability, MPFL reconstruction is effective for stabilizing the knee and may alone prevent lateral patellar dislocation. There is limited but growing evidence that MPFL reconstruction for patellofemoral instability leads to excellent functional outcomes. Growing awareness of the biomechanical contribution of the MPFL has led to an upsurge in the publication of techniques and trials dealing with reconstructive techniques, warranting a review that includes the most recent evidence. The aim of this article was to review and summarize the recent literatures concerning MPFL reconstruction and provide a comprehensive review of previous studies ranging from basic science to current surgical techniques and results.